Mobile Phone Utilization for Learning: Physics Teachers' Perception - Suyatna, Agus (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
The use of mobile phones for learning is still becoming a debate in Indonesia. Many schools forbid their students to bring mobile phones to school. This study was aimed to describe the perceptions of physics teachers in Lampung Province regarding the use of mobile phones to study physics. Data was collected from 39 physics teachers from various districts in Lampung Province. The Likert scale with a range of 1 to 5 was used. Descriptive quantitative data analysis was carried out. The results showed that most teachers agree /strongly agree: (1) to utilize mobile phones in learning physics both inside and outside of the classroom, (2) the tendency of students to use mobile phones make the physics learning process efficient. It could strengthen and improve the quality of the learning process. Almost all physics teachers agree /strongly agree with mobile phones usage, because: (1) it could turn the learning process from teacher-centered into student-centered and from content-oriented learning to process-oriented learning, (2) it could improve efficiency and productivity in the learning process. However, they agreed that the use of mobile phones by students could not replace the teacher's role, so physics teachers needed a more sophisticated concept of cellular learning to be implemented